Tissue distribution of phthalates in celery under different cultivation patterns and associated dietary exposure. (1st January 2022) - Zhao, Fang; Ma, Zhihong; Ping, Hua; He, Zhaoying; Li, Bingru; Gao, Yuan; Li, Cheng
Abstract: To investigate tissue distribution, spatial difference, temperature variation, and potential health risks of PAEs in vegetables, celery was used as a model plant. Celery samples were collected from open fields and greenhouses from two provinces in China over four seasons. Celery tissues were analyzed for 16 PAE compounds by gas chromatography–tandem mass spectrometry. The total content of PAEs was 89.0–1130.3 μg kg −1 dry weight (dw) in stems and 155.0–2730.8 μg kg −1 dw in leaves. Concentrations of PAEs in celeries showed notable spatial differences ( P  < 0.05), and the levels in samples from open fields were lower than those in samples from plastic greenhouses. In celeries from greenhouses, higher PAE concentrations were observed for plants grown at high temperatures than in plants grown at low temperatures. Discrepancies in tissue distribution indicated different uptake pathways of PAE contaminants. Risk assessments to humans found that both carcinogenic risks and non-carcinogenic risks of PAEs via celery consumption were at an acceptable level. Further research should consider other exposure pathways of PAEs and pay special attention to reducing PAE contents in vegetables. Graphical abstract: Image 1 Highlights: DiBP, DBP, and DEHP were prevalent and over 72% of 16 phthalates in celery. Phthalate levels in greenhouse celery were higher than in open-field celery. Tissue distribution and levels of phthalates in celery varied by season. Temperature greatly affected the major uptake pathway of phthalates in celery.